2010
DOI: 10.1590/s0101-20612010000200013
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas e sensoriais da carne de cordeiros Santa Inês terminados em dietas com diferentes níveis de caroço de algodão integral (Gossypium hirsutum)

Abstract: Original Recebido para publicação em 2/4/2008 Aceito para publicação em 4/1/2009 (003391) 1 Programa de Pós-graduação em Ciência e Tecnologia de Alimentos, Departamento de Tecnologia Química e de Alimentos, Universidade Federal da Paraíba -UFPB 2 Departamento de Tecnologia Química e de Alimentos, Universidade Federal da Paraíba -UFPB, Campus I, CEP 59059-900, João Pessoa -PB, Brasil, E-mail: msmadruga@uol.com.br 3 Empresa Estadual de Pesquisa Agropecuária da Paraíba -EMEPA, Rua Eurípides Tavares, no 210, CEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
2
11
0
5
Order By: Relevance
“…According to Teixeira et al (1987), for a product to be considered acceptable in terms of its sensory properties, it must present an index of acceptability of at least 70%. In this study, the lamb meat achieved good acceptability in all of the sensory attributes studied, since over 70% of the scores assigned were equal to or greater than 5, so they could be considered acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…According to Teixeira et al (1987), for a product to be considered acceptable in terms of its sensory properties, it must present an index of acceptability of at least 70%. In this study, the lamb meat achieved good acceptability in all of the sensory attributes studied, since over 70% of the scores assigned were equal to or greater than 5, so they could be considered acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed to the group treated with cottonseed there was a significant increase in values of b* (yellowness). However, Vieira et al (2010) observed linear increase in b * values in sheep meat according cottonseed level in the diet, this effect due gossypol which is a polyphenolic pigment rich in carotenoids that are deposited in adipose tissues of the muscle.…”
Section: Resultsmentioning
confidence: 94%
“…Vieira et al (2010) have used cottonseed until the level of 40% in the diet of sheep found no effect on the values of a * in the meat. The use of cottonseed in the cattle diet did not change the amount of total pigments ( Table 2).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations